1999
DOI: 10.1515/jpm.1999.012
|View full text |Cite
|
Sign up to set email alerts
|

Is the liver of the fetus the 4th preferential organ for arterial blood supply besides brain, heart, and adrenal glands?

Abstract: In this study we compared the distribution of blood flow to the liver in growth-retarded fetuses whose estimated weight was < 5th centile with normal-weight fetuses. As expected, the relative venous blood flow to the liver was reduced, with blood flowing preferentially through the ductus venosus. However, the total blood supply seemed to be maintained by a concomitant, significant increase in arterial blood flow through the hepatic artery. Absolute flow velocities such as the peak, minimum diastolic and tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 9 publications
2
23
0
Order By: Relevance
“…This is in keeping with other mechanisms seen in such fetuses: reduced size of and shunting through the foramen ovale 7,20 , increased resistance in the pulmonary circuit 21 , with correspondingly less venous return to the left heart, and retrograde blood flow at the aortic isthmus 7,22 to further supply the aortic arch and carotid arteries with right ventricular blood via the ductus arteriosus. A shift to the left of the watershed area between portal and umbilical venous supply to the liver 23,24 and an augmented blood velocity in the hepatic artery 25 will change the fetal circulation in the same direction. These are mechanisms of redistribution but also of increased recirculation of umbilical blood in the fetal body, which correspond to more extensive oxygen extraction.…”
Section: Discussionmentioning
confidence: 99%
“…This is in keeping with other mechanisms seen in such fetuses: reduced size of and shunting through the foramen ovale 7,20 , increased resistance in the pulmonary circuit 21 , with correspondingly less venous return to the left heart, and retrograde blood flow at the aortic isthmus 7,22 to further supply the aortic arch and carotid arteries with right ventricular blood via the ductus arteriosus. A shift to the left of the watershed area between portal and umbilical venous supply to the liver 23,24 and an augmented blood velocity in the hepatic artery 25 will change the fetal circulation in the same direction. These are mechanisms of redistribution but also of increased recirculation of umbilical blood in the fetal body, which correspond to more extensive oxygen extraction.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent study, Kiserud et al have demonstrated that in the human fetus, only 20Ϫ30 % of umbilical vein blood volume are actually transported through the ductus venosus, the other two thirds of the oxygen-rich blood are transported towards the liver and into the hepatic microcirculation. This is supported by a study investigating venous and arterial blood flow to the fetal liver, in which Kilavuz et al have proposed the concept of the fetal liver als the "4 th preferential organ" after the brain, the coronaries and the adrenal glands [17]. The proportion of umbilical vein blood advancing through the ductus venosus actually decreases near term [21].…”
Section: Ductus Venosusmentioning
confidence: 87%
“…Concerning the change of arterial blood flow in the fetus in cases of low placental perfusion with or without hypoxemia for years, heart, brain and adrenals were looked upon as the only three preferential organs for arterial blood supply. Meanwhile, spleen and liver, two organs receiving blood via the coeliac truncus were added to the organs with preferential arterial blood supply (Kilavuz and Vetter 1999). Even when assuming less extreme haemodynamic changes in addition with hypoxia in the children of our study these alterations could lead to a decrease of elastin synthesis in placental stem villus blood vessels.…”
Section: Discussionmentioning
confidence: 99%